Synthesis of Symmetrical Acetophenone Azine Derivatives as Colorimetric and Fluorescent Cyanide Chemosensors - Nur Masyittah Irmi; Bambang Purwono; Chairil Anwar (Universitas Gadjah Mada, 2021)
Cyanide is a highly toxic anion and poison to the environment. Therefore, fast, effective, and efficient analysis methods to detect cyanide are needed. Herein, symmetrical chemosensor of 2’-hydroxy acetophenone azine (1) and 2’,4’-dihydroxy acetophenone azine (2) has been synthesized tested as colorimetric and fluorescent cyanide chemosensor. The azines were produced from the condensation of acetophenone derivatives with hydrazine hydrate in ethanol under reflux or ultrasonic irradiation methods. Colorimetric and fluorescent chemosensor tests showed selectivity to acetate and cyanide anions in DMSO. The limit of detection (LOD) for colorimetric measurement of cyanide anion was 9.68×10–4 M for compound (1) and 9.63×10–5 M for compound (2), while the fluorescent method showed 15.90×10–4 M for compound (1) and 8.95×10–5 M for compound (2), respectively. In addition, test paper-strips containing sensor 2 indicated noticeable results for 'naked eye' detection of cyanide in an aqueous medium.